Pengelompokan Pelanggan Pdam Berdasarkan Penggunaan Air Oleh Konsumen Menggunakan Algoritma K-Medoids - Andi Prasetio Rozali Toyib; Sastya H Wibowo; Yulia Darnita (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The Regional Water Company (PERUMDA) Tirta Hidayah in Bengkulu City is a regional company engaged in providing clean water distribution services to the community. The problem addressed in this research is the difficulty of the company in meeting the water needs of its customers due to the lack of accurate and periodic data on water usage by customers, resulting in a lack of reference for the provision of clean water supply each month regarding the excess or shortage of water usage and the areas that use a lot or a little of clean water. This research aims to segment PDAM customers based on consumer water usage using the k-medoids algorithm. Customer water usage data from January to December 2022 were obtained from PDAM. Segmentation was performed using the k-medoids algorithm with Euclidean distance as the metric. The results of this research include the development of a system that can segment water usage of customers into wasteful and normal categories using the k-medoids method. The collected customer data can be segmented into several groups based on the same water usage patterns. The k-medoids algorithm can help segment customers into several clusters or groups with the same characteristics in terms of water usage.